Museu Paiter A Soe: a preservação da cultura indígena Paiter Suruí na Aldeia Gapgir, Cacoal/RO - Morais, Tatielle Aparecida Pinto Flores (2024)
This dissertation proposes a study of the creation and significance of the Paiter A Soe Museum for the Paiter Suruí people of the Sete de Setembro Indigenous Land, in the Gapgir Village, Line 14, Cacoal/RO. In addition, it aims to reflect on the importance of orality as an indigenous cultural tradition and historical source. The museum's objectives are to disseminate Paiter Suruí culture, recover the knowledge of elders, train younger generations in cultural preservation, and promote heritage education activities for both internal and external audiences. The Paiter Suruí are one of the indigenous ethnic groups living in the states of Rondônia and Mato Grosso, in the Legal Amazon region of Brazil. Over the years, "Paiter" has become a self-denomination meaning "real people" or "true people." They are also known as "Suruí," "Suruí Paiter," or "Suruí of Rondônia." This study addresses the importance of preserving the culture of the Paiter Suruí people, especially through oral history and the Paiter A Soe Museum, focusing on the museum's importance for preserving culture, oral tradition, and physical collections, which have been threatened by deforestation and the weakening of the transmission of traditions between generations. The main research problems include maintaining the museum in the village and raising awareness of its importance to the Paiter Suruí culture. The study utilizes books written by indigenous people: *Histórias do Começo e do Fim do Mundo – O contato do povo Paiter Suruí* (2016) and *Na Imensidão da Floresta: Gakamam Suruí e suas Memórias* (2020). In addition to non-Indigenous researchers who write about the Paiter ey, we have the books: Nós Paiter – Os Suruí de Rondônia (1985) and Vozes da Origem (2007), by anthropologist Betty Mindlin, the latter written with Suruí Paiter narrators, and Os Paiter Suruí – do arco e flechas às tecnologias do século XXI (2022), by historian Zeus Moreno Romero. For research in the field of oral history, the book Manual de História Oral (2013) by Verena Alberti is a methodological reference. Raising awareness about the importance of the museum and the preservation of Paiter Suruí culture is essential to ensure that ancestral traditions and knowledge are transmitted and valued. Thus, this dissertation not only documents aspects of the history and challenges faced, but also presents practical solutions for cultural preservation, highlighting the museum's relevance as a central pillar in this mission.